PENGARUH PEMBERIAN AIR REBUSAN DAUN MINT TERHADAP FREKUENSI EMESIS PADA IBU HAMIL TRIMESTER I - Siswi Wulandari (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2020)
Emesis in pregnancy is a condition where the mother experiences excessive nausea and vomiting. More than 70% of pregnant women suffer from this complaint in trimester 1. Based on a preliminary study to 10 pregnant women with emesis, as many as 2 (20%) pregnant women consume the drug to reduce nausea, and 8 (80%) Still experiencing nausea. The purpose of the research is to know the influence of water-boiling mint leaves against emetic in pregnant women in the Sukorame Puskesmas in Kediri City. This research is pre-experiment research with one group Pretest-posttest design. The population is the pregnant women trimester 1 in Sukorame Puskesmas and the sample in the study is all the pregnant women of TM 1 in Sukorame Puskesmas. The sampling techniques used the total population, with the instrument using an observation sheet. Based on the test Wilcoxon obtained a significant value of p value = 0.001, so it can be concluded that there is the influence of the water-boiling mint leaves to the emetic frequency in the 1st trimester pregnant women. Hope researchers can increase the participation to reduce the occurrence of emetic in pregnant women trimester 1 by consuming the water stew mint leaves